MoSe2 enriched with borophene towards promotion of electroactivity of Hydrogen Evolution Reaction – in situ and post mortem studies - Daria Baranowska; Jolanta Woronowska; Paweł Sać; Ewa Mijowska (Materials & Design)
Fossil fuels remain integral to modern life, powering nearly every public sector. However, growing concerns about their environmental impact and eventual depletion have accelerated the search for alternative energy sources. Among these, hydrogen fuel emerged as a promising candidate due to its high energy density and environmentally friendly nature. Therefore, in this contribution, we present a facile one-step fabrication route of MoSe2/borophene composite (MoSe2/B) and evaluate its electrochemical performance as a two-dimensional/two-dimensional (2D/2D) hybrid electrocatalyst for the hydrogen evolution reaction (HER). Remarkably, the MoSe2/B composite achieved an overpotential of 220 mV at 10 mA/cm2 with a Tafel slope of 62 mV/dec, outperforming reference samples significantly. In-situ Raman spectroscopy and post-mortem analyses reveal active participation of 2H and 1T phases of MoSe2 in different stages of hydrogen evolution reaction. Additionally, the presence of B2O3 and interfacial boron species suggests possible enhancements of the electrochemical activity of MoSe2/B through defect formation and surface modification. Therefore, this work highlights the potential of metal-free electrocatalysts in the promotion of HER processes, making a milestone forward to efficient and sustainable energy conversion systems.